Transformation of digital and management strategy for 'buletin jurnalis.com' news management in the online media Industry in Pali regency - Febrian, Heru; Misnawati, Desy; Isnawijayani, Isnawijayani; Jabir, Bastian (Jurnal Ekonomi, 2024)
The rapid advancement of technology has dramatically changed the media landscape, prompting the media industry to undergo digital transformation. The objective of this research is to discuss the digital transformation experienced by the online news platform "BuletinJurnalis.com" and its news management strategies within the context of the online media industry. The theoretical framework employed to analyze this research is media technology and convergence theory. The research method employed is qualitative descriptive with a case study approach. Data collection was conducted through in-depth interviews with five key informants, including the leadership, editor-in-chief, editorial management, news editor, and media correspondents from "BuletinJurnalis.com." The research findings reveal that "BuletinJurnalis.com" has taken bold steps in its digital transformation by integrating technology into all aspects of news production. Their strategies in news management include a fresh approach to writing, curation, and content distribution, emphasizing the importance of constant adaptation and innovation to maintain relevance and competitiveness. In conclusion, digital transformation and news management strategies play a pivotal role in shaping the future of media in the era of the online media industry.